A Novel And Improved Technique For Clustering Uncertain Data (International Journal of Engineering and Computer Science, 2015)
Clustering on uncertain data, one of the essential tasks in data mining. The traditional algorithms like K-Means clustering, UK Means clustering, density based clustering etc, to cluster uncertain data are limited to using geometric distance based similarity measures and cannot capture the difference between uncertain data with their distributions. Such methods cannot handle uncertain objects that are geometrically indistinguishable, such as products with the same mean but very different variances in customer ratings. In the case of K medoid clustering of uncertain data on the basis of their KL divergence similarity, they cluster the data based on their probability distribution similarity. Several methods have been proposed for the clustering of uncertain data. Some of these methods are reviewed.Compared to the traditional clustering methods, K-Medoid clustering algorithm based on KL divergence similarity is more efficient. T